Flash sintering of 3YSZ and in-situ joining with 304 stainless steel using copper as an interlayer. (15th March 2021) - Cao, Yue; Xu, Guo-Cheng; Li, Lin; Mao, Hai-Rong; Guo, Rui-Fen; Shen, Ping
Abstract: We demonstrated the feasibility of flash sintering of 3 mol% yttria-stabilized zirconia (3YSZ) and its in-situ joining with metal by applying an electric field. Herein, rapid densification of 3YSZ and its robust joining with 304 stainless-steel by using copper as a soft interlayer were achieved under a preset alternating current/direct current (AC/DC) field within only 1 min at 950 °C. Nevertheless, defects were present in the microstructures of the joints under the application of a single AC or DC field. The sintering-joining mechanisms were addressed in view of electric field-induced Joule heating and internal electrochemical reaction. Graphical abstract: Image, graphical abstract